(untitled) (Bodhi Path, 2022)
The Sanskrit term ‘Vidyā’ as shown in the above-mentioned Sanskrit saying, is rendered into English as ‘Science, Field of Study or Field of Knowledge’ which generally refers to an understanding of or information about a subject that one acquires by dint of experience or study. It also means what is learned, understood or aware of. This Science is divided into two: theoretical and practical, or traditional and modern. From the Indian traditional point of view, the entire Mahāyāna Buddhist literature is preserved in three corpus— Kagyur, Tengyur and Sungbum. Among the three, Kagyur contains 1115 literature classifying in nine categories, Tengyur contains 3387 classifying in 15 categories while Sungbum contains more number. The number of category of the former two may differ from edition to edition. The subject matter or contents of the huge corpus of the literature is subsumed in the five sciences. Their objective is to pave a way to liberation. They are indispensible for the sake of providing correct understanding and view to men so that they may get through or come out from the vicious cycle of saṁsāra as well as for eliminating the miseries from their roots. The absence of right knowledge, the affect of wrong view is ignorance. The purpose of the Vidyā (science) is to show a path how to get rid of the darkness of ignorance. As per the other Indian traditions, Buddhist traditions also have their respective systems of learning, teaching and practising sādhāna as well as a particular presentation of science. Both the Theravāda and Mahāyāna systems give the highest value to the Science. However, the system varies in the Presentation of Science set up by the two main traditions. The presentation of Mahāyāna Science is popular in the name of ‘The Five Sciences (Five Major Sciences), though it also has the presentation of five minor sciences.